2009
DOI: 10.1159/000279385
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-Targeted Short Hairpin RNA Inhibits Intraperitoneal Ovarian Cancer Growth in Nude Mice

Abstract: Objective: In this study, we inhibited the expression of VEGF by short hairpin RNA (shRNA) in SKOV3 ovarian cancer cells in vitro and in vivo to explore the antitumor efficacy of shRNA in ovarian cancer cells. Methods: ShRNA targeting VEGF was cloned into pGenesil-2 plasmid vector and then transfected into SKOV3 ovarian cancer cells using liposome. Silencing of VEGF expression was measured by RT-PCR and ELISA assays. Furthermore, the growth inhibition capacity of shRNA on SKOV3 intraperitoneal ovarian carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Tumor volumes were measured every 2 days during treatment duration until animals were sacrificed, and no animal death or signs of possible toxicity were observed during this period (data not shown) [34]. Although the tumors of all mice were approximately equal in initial volumes, significant differences in tumor growth were observed upon treatment with PGAM1-shRNA-a.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor volumes were measured every 2 days during treatment duration until animals were sacrificed, and no animal death or signs of possible toxicity were observed during this period (data not shown) [34]. Although the tumors of all mice were approximately equal in initial volumes, significant differences in tumor growth were observed upon treatment with PGAM1-shRNA-a.…”
Section: Resultsmentioning
confidence: 99%
“…The signals were quantified by QuantityOne software (Bio-Rad) and defined as the ratio of target protein to ␤-actin. ELISA was used to measure VEGF concentration in conditioned medium as described elsewhere (15).…”
Section: Methodsmentioning
confidence: 99%
“…Pain assessment was done with a 10-point linear analog scale, with 0 representing no pain and 10 representing the worst possible pain. The serum CA12-5 levels of 30 adenomyosis patients (these 30 patients also fell into those 65 patients whose endometrial tissues were further subjected to immunohistochemical analysis) were analyzed using ELISA as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies demonstrated that siRNA-mediated silencing of oncogenes induces growth arrest and death of tumor cells, indicating their potential therapeutic value [4-7]. Although siRNAs are gene specific, they are not cell/tissue-selective and therefore can not specifically target or accumulate in tumor tissues.…”
Section: Introductionmentioning
confidence: 99%